Survival after Radical Prostatectomy versus Radiation Therapy in High-Risk and Very High-Risk Prostate Cancer. Issue 2 (24th February 2022) - Chierigo, Francesco; Wenzel, Mike; Würnschimmel, Christoph; Flammia, Rocco Simone; Horlemann, Benedikt; Tian, Zhe; Saad, Fred; Chun, Felix K. H.; Graefen, Markus; Gallucci, Michele; Shariat, Shahrokh F.; Mantica, Guglielmo; et al.
Abstract : Purpose: Our goal was to compare cancer-specific mortality (CSM) rates between radical prostatectomy (RP) vs external beam radiotherapy (EBRT) in National Comprehensive Cancer Network© (NCCN©) high risk (HR) patients, as well as in Johns Hopkins University (JH) HR and very high risk (VHR) subgroups. Materials and Methods: Within the Surveillance, Epidemiology, and End Results database (2010–2016), we identified 24, 407 NCCN HR patients, of whom 10, 300 (42%) vs 14, 107 (58%) patients qualified for JH HR vs VHR, respectively. Overall, 9, 823 (40%) underwent RP vs 14, 584 (60%) EBRT. Cumulative incidence plots and competing-risks regression addressed CSM after 1:1 propensity score matching (according to age, prostate specific antigen, clinical T and N stages, and biopsy Gleason score) between RP and EBRT patients. All analyses addressed the combined NCCN HR cohort, as well as in JH HR and JH VHR subgroups. Results: In the combined NCCN HR cohort 5-year CSM rates were 2.3% for RP vs 4.1% for EBRT and yielded a multivariate hazard ratio of 0.68 (95% CI 0.54–0.86, p <0.001) favoring RP. In VHR patients 5-year CSM rates were 3.5% for RP vs 6.0% for EBRT, yielding a multivariate hazard ratio of 0.58 (95% CI 0.44–0.77, p <0.001) favoring RP. Conversely, in HR patients no significant difference was recorded between RP vs EBRT (HR 0.7, 95% CI 0.39–1.25, p=0.2). Conclusions: Our data suggest that RP holds a CSM advantage over EBRT in the combined NCCN HR cohort, and in its subgroup of JH VHR patients.